Revolution Technology Digital Change Aspects of Life - Jukhri Syah Putra Bancin (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Various aspect life man has changed in a way significant by revolution technology digital. Digital technology has created opportunities and new obstacles in many ways, such as the way people interact One The same other, Work, Study, And get service health. In article This, we will discuss how the digital technology revolution impacts areas such as economics, education, social interactions, and data security and privacy issues. This study finds ways in which technology digital increase productivity, efficiency, And inclusion. They Also find problem that need to be considered. They use literature study methods and secondary data analysis.